A head-to-head comparison of laser vs. powered mechanical sheaths as first choice and second line extraction tools. Issue 2 (10th November 2022) - Zsigmond, Elod-Janos; Saghy, Laszlo; Benak, Attila; Miklos, Marton; Makai, Attila; Hegedus, Zoltan; Alacs, Endre; Agocs, Szilvia; Vamos, Mate
Abstract: Aims: During transvenous lead extraction (TLE) longer dwelling time often requires the use of powered sheaths. This study aimed to compare outcomes with the laser and powered mechanical tools. Methods and results: Single-centre data from consecutive patients undergoing TLE between 2012 and 2021 were retrospectively analysed. Efficacy and safety of the primary extraction tool were compared. Procedures requiring crossover between powered sheaths were also analysed. Moreover, we examined the efficacy of each level of the stepwise approach. Out of 166 patients, 142 (age 65.4 ± 13.7 years) underwent TLE requiring advanced techniques with 245 leads (dwelling time 9.4 ± 6.3 years). Laser sheaths were used in 64.9%, powered mechanical sheaths in 35.1% of the procedures as primary extraction tools. Procedural success rate was 85.5% with laser and 82.5% with mechanical sheaths ( P = 0.552). Minor and major complications were observed in similar rate. Procedural mortality occurred only in the laser group in the case of three patients. Crossover was needed in 19.5% after laser and in 12.8% after mechanical extractions ( P = 0.187). Among crossover procedures, only clinical success favoured the secondary mechanical arm (87.1 vs. 54.5%, aOR: 0.09, 95% CI: 0.01–0.79, P = 0.030). After step-by-step efficacy analysis, procedural success was 64.9% with the first-line extraction tool, 75.1% after crossover, 84.5% with bailout femoral snare, and 91.8% by non-emergency surgery. Conclusion: The efficacy and safety of laser and mechanical sheaths were similar, however in the subgroup of crossover procedures mechanical tools had better performance regarding clinical success. Device diversity seems to help improving outcomes, especially in the most complicated cases. Graphical Abstract: Graphical Abstract